What Fed funds futures tell us about monetary policy uncertainty - Jean-Sébastien Fontaine (Bank of Canada, 2016)
The uncertainty around future changes to the Federal Reserve target rate varies over time. In our results, the main driver of uncertainty is a "path" factor signaling information about future policy actions, which is filtered from federal funds futures data. The uncertainty is highest when it signals a loosening cycle. The uncertainty raises the risk premium in a loosening cycle, reducing the transmission of target changes to longer maturities. Our results trace the information content of federal funds futures to hedging demand.
Keywords: E43; E44; E47; G12; G13; 330; Asset pricing; Financial markets; Interest rates